Bagaimana Bisnis Menghadapi Perubahan Algoritma Media Sosial: Strategi Bertahan di Era Digital yang Mudah Berubah (Jurnal Riset Manajemen dan Akuntansi, 2025)
This study discusses how small and medium enterprises (SMEs) in Pontianak respond to changes in social media algorithms without using paid advertising. It employs the Dynamic Capabilities framework, which includes sensing (monitoring changes), seizing (taking advantage of opportunities), and reconfiguring (adjusting strategies), along with the concept of Algorithmic Gatekeeping. The study uses a qualitative approach through case studies and thematic analysis. Data were obtained from literature reviews, purposive participant selection, data collection via Google Forms, document analysis, and direct observation. The findings show that SMEs recognize algorithm changes through declines in organic content reach and shifting preferences for certain content formats favored by platforms. In response, they combine short videos with longer, informative content, experiment with posting times, use trending hashtags, and vary content formats without incurring additional costs. Content performance is evaluated before and after implementing strategies as part of a continuous learning process. The results indicate that SMEs with limited resources can still compete by applying adaptive, data-driven content strategies. This study highlights the importance of continuous learning cycles, monitoring content trends, and maintaining flexibility in format choices so that SMEs remain relevant and resilient amid the ongoing evolution of social media algorithms.